Hybrid joining of steel and plastic materials by laser beam - Bauernhuber, Andor; Markovits, Tamás (Transport, 2014)
Hybrid joining of metals and plastics in order to produce lightweight parts is of growing interest in the manufacturing processes of vehicles, electrical devices and biomedical applications. In this study, the joining of PMMA plastic (poly methyl metacrylate) and unalloyed steel were investigated by the authors. The authors successfully joined PMMA and steel by means of Nd:YAG laser and carried out tensile tests to measure the joining strength. Experimental results showed that the joint strength is influenced by the heating time, the penetration depth of the steel workpieces in the plastic, by the surface roughness of steel and by the time elapsed between bonding and tearing of the samples.First published online: 22 May 2013